The Use of Image Media in Indonesian Language Learning to Improve Reading Skills in Elementary Schools - Riska Kurniati; Eny Munisah; Sumarno (LPPM Undiksha, 2025)
Students' reading ability still faces obstacles such as low reading interest and less interesting learning methods. This study uses a literature review to analyse the use of image media in Indonesian language learning to improve reading skills in elementary schools. The method used in this study is a systematic literature review using data accessed from Google Scholar. The research applied in this analysis consists of articles published from 2020-2024. For the initial search based on keywords, we found as many as 11,700 documents using the keyword